Review on Pharmaceutical Quality by Design (QbD) - Deepak Kumar, Deepak; Ancheria, Rahul; Shrivastava, Saumya; Soni, Shankar Lal; Sharma, Mukesh (Asian Journal of Pharmaceutical Research and Development, 2019)
Pharmaceutical Quality by Design (QBD) is a systematic approach to development that begins with predetermined objectives and emphasizes the understanding of production and processes and process control, based on sound science and quality risk management. Quality purchasing design (QBD) is emerging to increase the promise of providing safe and effective medicines to customers and promises to improve the efficiency of product quality. Quality means eligibility for use. The quality of the medication means that the product provides therapeutic benefits to the label reproducible and free from contamination on the label. In vivo or in vitro performance test can be evaluated for drug production. Dinette by Quality guarantees the performance of the product in vitro and the performance of the in vitro product in the in vivo product. So the quality design is related to the product.